Pectobacterium atrosepticum and Pectobacterium carotovorum Harbor Distinct, Independently Acquired Integrative and Conjugative Elements Encoding Coronafacic Acid that Enhance Virulence on Potato Stems - Panda, Preetinanda; Vanga, Bhanupratap R.; Lu, Ashley; Fiers, Mark; Fineran, Peter C.; Butler, Ruth; Armstrong, Karen; Ronson, Clive W.; Pitman, Andrew R. (Frontiers in Microbiology, 2016)
Integrative and conjugative elements (ICEs) play a central role in the evolution of bacterial virulence, their transmission between bacteria often leading to the acquisition of virulence factors that alter host range or aggressiveness. Much is known about the functions of the virulence determinants that ICEs harbor, but little is understood about the cryptic effects of ICEs on their host cell. In this study, the importance of horizontally acquired island 2 (HAI2), an ICE in the genome of Pectobacterium atrosepticum SCRI1043, was studied using a strain in which the entire ICE had been removed by CRISPR-Cas-mediated genome targeting. HAI2 encodes coronafacic acid, a virulence factor that enhances blackleg disease of potato stems caused by P. atrosepticum SCRI1043. As expected, deletion of HAI2 resulted in reduced blackleg symptoms in potato stems. A subsequent screen for HAI2-related ICEs in other strains of the Pectobacterium genus revealed their ubiquitous nature in P. atrosepticum. Yet, HAI2-related ICEs were only detected in the genomes of a few P. carotovorum strains. These strains were notable as blackleg causing strains belonging to two different subspecies of P. carotovorum. Sequence analysis of the ICEs in different strains of both P. atrosepticum and P. carotovorum confirmed that they were diverse and were present in different locations on the genomes of their bacterial host, suggesting that the cfa cluster was probably acquired independently on a number of occasions via chromosomal insertion of related ICEs. Excision assays also demonstrated that the ICEs in both P. atrosepticum and P. carotovorum are mobilised from the host chromosome. Thus, the future spread of these ICEs via lateral gene transfer might contribute to an increase in the prevalence of blackleg-causing strains of P. carotovorum.